The Influence of Institutional Ownership, Profitability, and Company Size on Earnings Quality - Tsania, Aida Ayu Faiza; Mudjiyanti, Rina; Santoso, Suryo Budi; Santoso, Selamet Eko Budi (Universitas Pamulang, 2025)
The increasingly competitive business environment demands greater transparency in financial information, particularly earnings reports, which serve as a foundation for economic decision-making by various stakeholders. Nonetheless, not all reported earnings can be considered high-quality, making it essential to examine the factors that influence the quality of earnings. The banking sector plays a vital role in the national economy; however, gaps in corporate governance practices, as reflected in instances of financial statement manipulation in Indonesia. This study aims to examine the impact of institutional ownership, profitability, and company size on earnings quality in the banking industry. A quantitative approach was employed. The population consists of banking sector companies listed on the Indonesian Stock Exchange. A sample study was selected using purposive sampling. A total of 46 companies met the criteria, yielding 184 observations; which is the final sample comprised 57 observations after removing outliers. Multiple linear regression analysis was employed as the analytical tool. The results indicate that institutional ownership has a significant effect on earnings quality in the banking sector, while profitability and company size do not have a significant impact. This study is expected to serve as a reference for investors, regulatory authorities, and corporate management in enhancing accountability and transparency of financial information in the banking sector.